EFFECT OF FIBRE TYPE AND VOLUME FRACTION ON THE STRENGTH OF ADVANCED HIGH-STRENGTH CONCRETE - Prasad Sonar; Dnyaneshwar B. Mohite (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The demand for High-Strength Concrete (HSC) in modern infrastructure has grown due to its superior compressive strength and reduced section sizes. However, its inherent brittleness and limited tensile capacity present significant design and durability challenges. This study aims to evaluate the influence of different steel fibre types and their volume fractions on the mechanical performance of HSC across three advanced concrete grades M70, M80, and M90. The investigation employs three distinct steel fibre types: Sound Crimped Steel Fibres (SCSF), Hooked End Steel Fibres (HESF), and Flat Steel Fibres (FSF), with volume fractions varying from 0.5% to 4.0% by weight of cementitious material. Supplementary cementitious materials such as silica fume and fly ash were incorporated to further refine the mix design and enhance the composite action of fibres. A total of 243 specimens, including cubes, cylinders, and prisms, were tested to assess compressive strength, split tensile strength, and flexural strength at 28 days. Results demonstrated a marked improvement in all strength parameters with fibre addition, particularly at 3% volume fraction. Among the fibre types, FSF exhibited superior performance in flexural strength, while HESF contributed most effectively to compressive strength enhancements. The study confirms that fibre type and dosage significantly influence the mechanical behavior of high-strength concrete and that an optimal balance between workability, strength, and ductility can be achieved through careful selection of fibre characteristics. These findings offer practical implications for the design of high-performance concrete in critical structural applications.